Aplicação da gestão de processos em uma universidade pública do estado de São Paulo - Rodrigues, Gustavo de Oliveira [UNESP] (2015)
The business Process Management (BPM) is one of the current issues in the information age, because on the one hand, it addresses the interaction of people and organizations and on the other, recognition software processes. BPM unites business management of organizations to use methods, techniques and modeling tools, publication, control and analysis of business processes involving people and different systems. This work presents a literature review of processes, business processes, management of business processes, management of business processes, management of business processes in public organizations, structuring and process modeling, business process maturity and the major languages and tools for modeling business processes in order to see how BPM can help improve the processes of a Public University of São Paulo State, in addition to identifying and limiting potential barriers to the use of BPM in this context. For this, the comparision of some languages of process modeling and some modeling software processes to identify the best tools for the development modeling and some modeling software processes to identify the best tools for the develpment of this work was performed. After, we proceeded with the implementation of the BPM lifecycle management, through the stages of planning, modeling and optimization and implementation of processes. Besides the benefits of application of BPM, such as reduced time and processes running costs, increased knowledge about the process, bureaucracy reduction for its implementation and automation of processes through the development of a management software processes were found limitations for its implementation, such as the organizational structure of a public university, the number and complexity of cases, the level of maturity in which the proceedings are, cultural issues and resource constraints for acquisition of suitable tools for deploying BPM